RESPON PEMBENTUKKAN KALUS EMBRIONIK TANAMAN KRISAN KULO (Chrysanthemum morifolium) TERHADAP PEMBERIAN ZAT PENGATUR TUMBUH SITOKININ - Juita S. Sinaulan; Edy F. Lengkong; Stella Tulung (COCOS, 2018)
ABSTRACT Growth regulating substances are organic or inorganic compounds that play an important role in biological processes in plant tissue and one of them is embryonic callus formation and embryogenesis. This study aims to determine the effect of the administration of growth regulators cytokines at certain concentrations on the formation of embryonic callus of chrysanthemum plants. This research was conducted at the Genetics Laboratory of the Faculty of Agriculture, Sam Ratulangi University, Manado. The research was conducted for 4 (four) months, starting June 2018 to October 2018. The research method was carried out using a completely randomized design using the growth regulator from cytokinins, namely zeatin (Z) and TDZ (T) with the concentrations used were 2 ppm, 4ppm and 6ppm, each of which added auxin ZPT 1AA 0.02 Ppm and GA3 O, 2 ppm and repeated 5 times. The variables observed were callus formation time, callus wet weight, and callus color. The results showed that the the callus formation time in chrysanthemum culture was the fastest is 7,8 days after culture, which was treated with zeatin 2 ppm, the largest wet weight culture was 2.111 gr at the treatment of 2 ppm TDZ and the color of the callus formed was green. Keywords : Growth Regulating Substances, Embryonic Callus